A comprehensive checklist of the Colombian Campylocentrum sect. Campylocentrum (Orchidaceae, Vandeae, Angraecinae) with a new species - Pessoa, Edlley M. (Phytotaxa, 2020)
This study provides a comprehensive checklist of the Colombian species of Campylocentrum sect. Campylocentrum based on an analysis of 20 herbaria around the world that house specimens from the country. Complete type citations, synonymy list, list of representative specimens, distribution maps, identification key, and taxonomic notes on species similarities are provided. Neglected in these herbaria, a new species, C. alvesii, is described and illustrated. Ten species of the section are confirmed to Colombia, here C. carlos-parrae, C. escobariae, C. chocoense, and C. queremalense are synonymized, and C. polystachyum is confirmed for the country.